Clinical Use of PanoMap for Glaucoma: Frequently Damaged Areas in Early Glaucoma. Issue 1 (January 2021) - Lee, Won June; Shin, Yong Un; Lim, Han Woong; Cho, Heeyoon; Park, Ki Ho; Seong, Mincheol
Abstract : Précis: Recognizing the shortcomings of poor consistency of the fovea-disc relationship at different time points and comparing PanoMaps may well facilitate the understanding of the spatial relationship between parapapillary and macular areas in glaucoma. Purpose: The aims of this study are to analyze the spatial distribution of the frequently damaged areas in early glaucoma, compare the patterns between nonprogressors and progressors using the combined wide-field parapapillary and macular deviation maps (PanoMap), and to evaluate the consistency of the fovea-disc relationship in PanoMap. The fovea-disc distance (FDD) and fovea-disc axis (FDA) were compared at baseline and at the last follow-up. Materials and Methods: In total, 118 patients with early glaucoma and a minimum follow-up period of 3 years were included in this retrospective observational study. The pattern of structural changes was evaluated by averaging the PanoMaps of the enrolled patients at baseline and last follow-up. Longitudinal comparison of the FDD and FDA was performed at baseline and the last follow-up. Patients were divided into nonprogressor (n=44) and progressor (n=74), and the patterns of glaucoma progression in PanoMaps were compared between them. Results: At baseline, the glaucomatous damage was found more frequently in the macular compared with the parapapillary area. The spatial distribution of frequently damaged areas was similar between the nonprogressor and progressor. At the last follow-up, compared with the baseline structural change on the PanoMap, the progressive structural changes extended toward the fovea at both the parapapillary and macular areas in the progressor. The FDD and FDA were significantly different between the baseline and the last follow-up. Conclusions: The PanoMaps showed a clear spatial distribution of early glaucomatous changes, indicating that the damaged area was frequently observed in the macular area. As the consistency of the fovea-disc relationship in PanoMaps was not excellent, this aspect should be considered when interpreting the PanoMap. Abstract : Supplemental Digital Content is available in the text.